Regular Trace Event Structures - Thiagarajan, P. S. (BRICS Report Series, 1996)
We propose trace event structures as a starting point for constructing effective branching time temporal logics in a non-interleaved setting. As a first step towards achieving this goal, we define the notion of a regular trace event structure. We then provide some simple characterizations of this notion of regularity both in terms of recognizable trace languages and in terms of finite 1-safe Petri nets.